Dispositional mindfulness profiles in pregnant women: relationships with dyadic adjustment and symptoms of depression and anxiety - Echabe-Ecenarro, Oiana; Orue, Izaskun; Calvete, Esther (Frontiers in Psychology, 2023)
Pregnancy is a time of major transition that can be stressful for women. Dispositional mindfulness may protect individuals when they face stress. Recent studies have adopted a person-centered approach to examine the role of mindfulness by identifying subtypes of individuals based on their scores in five mindfulness facets. Latent profile analysis was used to identify different mindfulness profiles in a sample of pregnant women, and we explored the relationships between these profiles, depression and anxiety symptoms, and whether dyadic adjustment mediated these relationships. A total of 535 women aged 18-45 years in their 26th week of pregnancy completed questionnaires regarding mindfulness, dyadic satisfaction and cohesion, and depression and anxiety symptoms. Three profiles were identified: (1) low mindfulness (53.8%), (2) moderate mindfulness (34.3%), and (3) non-judgmentally aware (11.9%). The most adaptive profile was the non-judgmentally aware profile. Compared to the low mindfulness profile, the non-judgmentally aware profile and the moderate mindfulness profile were related to fewer symptoms of depression and anxiety, and these relationships were partly mediated by dyadic satisfaction. These results suggest that analyzing each pregnant woman's mindfulness profile can improve the prevention of and interventions for anxiety and depression.